Cholesterol depletion sensitizes gallbladder cancer to cisplatin by impairing DNA damage response. Issue 23 (2nd December 2019) - Zhang, Yonglong; Liu, Yanfeng; Duan, Jinlin; Wang, Hui; Zhang, Yuchen; Qiao, Ke; Wang, Jian
ABSTRACT: Gallbladder cancer (GBC) is the common malignancy of the bile tract system with extremely poor clinical outcomes, owing to its metastatic property and intrinsic resistance to the first-line drugs. Although it is well-established that cholesterol abnormity contributes to gallstone formation, a leading risk factor for GBC, the link of cholesterol homeostasis with GBC has not been investigated. The present study systematically examined the genes implicated in cholesterol homeostasis, and revealed altered gene expressions of de novo cholesterol biosynthesis and sterol sulfonation (SULT2B1), reduced bile acid synthesis (CYP7B1 and CYP39A1) and impaired sterol efflux (ABCA1, ABCG5, LCAT, and CETP) in GBC tissues. Suppression of cholesterol biosynthesis by lovastatin inhibited GBC cell proliferation possibly through attenuating the DNA repair process. Further investigation revealed lovastatin sensitized GBC cells to cisplatin-induced apoptosis and suppressed the activation of CHK1, CHK2, and H2AX during DNA damage response. By using chemically distinct statins, HMGCR depletion or supplementing mevalonate, the product of HMGCR, we showed the inhibitory effects on DNA repair process of lovastatin were due to the blockage of the mevalonate pathway. Subcutaneous xenograft mice model suggested lovastatin promoted the therapeutic efficacy of cisplatin, and significantly prolonged the survival times of tumor-bearing mice. Moreover, HMGCR ablation repressed tumor growth in vivo, which can be rescued partially by restored expression of HMGCR, suggesting the on-target effects of lovastatin. Therefore, our study provides the clinical relevance of cholesterol homeostasis with GBC progression, and highlights a novel intervention of combined use of lovastatin and cisplatin for GBC.